African Religio-Philosophical Paradigm as Tool for Moral Development in Nigeria - Austin, Omomia O. (NIU Journal of Humanities, 2020)
There is the consistent argument about the contemporary moral decadence in Nigeria, occasioned by an obvious erosion of initially held values and virtues. It is believed that the society was initially driven by traditionally accepted norms which were orchestrated by clear overt recourse to the African philosophical paradigm. It is quite impossible to extricate the African from his religion, which has tremendous relationship with his philosophy and culture. There is therefore, a clear nexus between the African religion and philosophical expressions. The position of this paper is that moral re-engineering in Nigeria can be achieved through the prism of African Religion and Philosophy. The re-awakening of moral rectitude can be achieved through a renewed recourse to African Religion and Philosophy, with the inherent components which are clear expressions of values, and outstanding virtues. The paper explores the religio-philosophical and cultural paradigm of the African in its methodology. It is thus recommended that the challenge of contemporary moral decadence in Nigeria can be redressed through renewed interest in exploring the value of African Religion and Philosophy. There is also the need to re-direct the citizens towards the tremendous importance of high moral disposition as a veritable tool in national development. The overall goal is to ensure that the nation scores high in her moral â€œtestâ€ as this will definitely impinge on sustainable development, and the much desired wellbeing of her citizens. The paper recommends among others that moral values should be inculcated into the youth from the home and supported by the school. This involves all stakeholders, that is the family, school, government and others. Keywords: African, Moral Development, Paradigm, Religio-Philosophical, Tool.